Efficacy versus effectiveness in clinical trials - Costa, M; Griffin, X; Parsons, N; Dritsaki, M; Perry, D (British Editorial Society of Bone and Joint Surgery, 2017)
The Bone & Joint Journal is keen on randomised clinical trials. The reason for this is straightforward. Randomisation is a simple and highly effective way of reducing the effects of ‘confounding factors’ in comparative research. Trauma and orthopaedic surgery has some of the most effective interventions in medicine. However, all surgical interventions are ‘complex’ in that they have many interacting facets which each contribute to the overall result. The selection of patients, the pre-operative pathway, the anaesthetic technique, the experience of the surgeon, the nursing and therapy staff, and even the hospital food, can all have an influence on the outcome. Any factor that is independently related to both the intervention and the outcome is called a ‘confounder’ (Fig. 1). Whilst some confounding variables can be identified and measured, such as the age of the patients, others may be unknown or difficult to measure, such as the influence of surgical expertise. Therefore, confounding is always a problem in trauma and orthopaedic research, even if we are able to match the patients taking part in a trial carefully.